Racially imbalanced peremptory challenges by the defense as a reactionary process - DeCamp, Elise (Crime & delinquency, 2022)
The use of peremptory challenges in American criminal trials has been found to be racially discriminatory despite race-based motivation being unconstitutional in jury selection. One argument made in defense of peremptory challenges is that the prosecution and the defense counteract each other, and “cancel out” each other’s impact. Using data from 208 criminal trials in Mississippi, this study examines whether the prosecution and defense counteract each other and what impact this has on juries. Findings suggest that the prosecution has a significant effect on the defense’s use of peremptory challenges. Although the average proportion of Black jurors is not significantly different as a result of peremptory challenges, the greater dispersion in proportions increases the volatility in jury composition.